Comparison of nutritional status among children with biliary atresia according to age at the time of Kasai procedure - Febricilla Citra Pratiwi; Titis Widowati; Endy Paryanto Prawirohartono (Indonesian Pediatric Society, 2019)
Background Recent studies revealed better outcomes among children with biliary atresia (BA) who underwent Kasai procedure at 60 to 90 days of age. Delayed Kasai procedure has a high risk of complications, including nutritional deficits which lead to malnutrition. Objective To determine the nutritional status of children with BA according to age at the time of Kasai procedure. Methods Using medical records, we conducted a retrospective study in children with BA based on magnetic resonance cholangiopancreatography (MRCP) or intraoperative cholangiography, who were admitted between 2015 to 2017 and underwent Kasai surgery at Dr. Sardjito General Hospital, Yogyakarta. Nutritional status was evaluated on the day before Kasai procedure, and classified into 4 groups of subjects based on age at the time the children underwent Kasai procedure (<60 days, 60-90 days, >90-120 days, and >120 days). Normal distribution data was analyzed with Saphiro-Wilk test and mean T-test was used to compare mean age at the time of Kasai procedure between groups of well-nourished and malnourished subjects. Results A total of 39 children with BA underwent Kasai procedure. Of 3 children who underwent Kasai procedure at <60 days of age, 2 were well-nourished and 1 was malnourished. Of the 12 children who underwent Kasai procedure at 60-90 days of age, 6 were well-nourished and 6 were malnourished. Of the 7 children who underwent Kasai procedure at >90-120 days of age, 4 were well-nourished and 3 were malnourished. Of 17 children who underwent Kasai procedure at >120 days of age, 5 were well-nourished and 12 were malnourished. The means of age at the time of Kasai procedure were higher in malnourished subject than well-nourished. Conclusion The highest prevalence of malnourishment is seen in children with biliary atresia who underwent Kasai procedure at >120 days of age.